CORRELATION BETWEEN METABOLIC SYNDROME AND URIC ACID LEVEL IN THE OFFICE WORKERS OF A BUMN COMPANY IN SURABAYA - Jihan Jauza Fairuz; Dewi Ratna Sari; Soebagijo Adi Soelistijo (Universitas Airlangga, Surabaya, Indonesia, 2021)
Background: Metabolic syndrome is a cluster of risk factor which consists of central obesity, hypertriglyceride, low High Density Lipoprotein (HDL) level, hypertension, and hyperglycemia. Its incidence among the office workers is increasing. Uric acid is often associated with cardiovascular disease while risk factor of cardiovascular disease is associated with metabolic syndrome. Objective: To analyze the correlation between metabolic syndrome and uric acid level in office workers. Materials and Methods: This study used medical record of health examination of PT Wijaya Karya Divisi IV male office workers aged of 20 – 60 years. The data taken consisted of abdominal circumference, blood pressure, triglyceride, HDL, fasting blood glucose, and uric acid levels. The diagnostic criterion of metabolic syndrome used in this study was National Cholesterol Education Program’s Adult Treatment Panel III (NCEP ATP III) that had been modified for Asians. The correlation of metabolic syndrome and serum uric acid level was analyzed by chi-square test with IBM SPSS Statistic 20 application. Results: There was no significant correlation (p=0.598) between metabolic syndrome and uric acid level in male office workers of PT Wijaya Karya Divisi IV. Conclusion: Metabolic syndrome and uric acid level among male office workers of PT Wijaya Karya Division IV had no correlation.